2009
DOI: 10.2353/ajpath.2009.080721
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Therapeutic Targets in Malignant Mesothelioma Using Cell-Cycle Gene Expression Analysis

Abstract: Cell-cycle defects are responsible for cancer onset and growth. We studied the expression profile of 60 genes involved in cell cycle in a series of malignant mesotheliomas (MMs), normal pleural tissues, and MM cell cultures using a quantitative polymerase chain reaction-based, low-density array. Nine genes were significantly deregulated in MMs compared with normal controls. Seven genes were overexpressed in MMs, including the following: CDKN2C, cdc6, cyclin H, cyclin B1, CDC2, FoxM1, and Chk1, whereas Ube1L an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 48 publications
(41 reference statements)
3
42
0
Order By: Relevance
“…Total RNA, isolated from 20 cases of NSCLC and matched normal tissue using reagent (Trizol; Invitrogen), was reverse transcribed 17 and analyzed for changes in Scrib mRNA expression relative to ␤2-microglobulin using TaqMan gene expression assays (Hs00363005_m1 and Hs99999907_m1, respectively; Applied Biosystems, Life Technologies Corporation, Carlsbad, CA), according to the 2 -⌬Ct formula.…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
“…Total RNA, isolated from 20 cases of NSCLC and matched normal tissue using reagent (Trizol; Invitrogen), was reverse transcribed 17 and analyzed for changes in Scrib mRNA expression relative to ␤2-microglobulin using TaqMan gene expression assays (Hs00363005_m1 and Hs99999907_m1, respectively; Applied Biosystems, Life Technologies Corporation, Carlsbad, CA), according to the 2 -⌬Ct formula.…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
“…Little is known about the regulation of the CAK complex though cyclin H [24,25]. Immunohistochemistry and real time quantitative polymerase chain reaction were used to determine cyclin expression and gene amplification in 219 tumors; the results indicated that cyclin H was overexpressed in all tumors [26][27][28]. These results mentioned above indicated that several biomarkers for cancer diagnosis can be found in a 2D-PAGE gel according to the approach describes hereto.…”
Section: Differential Protein Identificationmentioning
confidence: 79%
“…CDK1 knockdown could provide a novel therapeutic approach to arrest cell-cycle progression in MPM cells: in 2009 it has been observed that CDC2 silencing increased the apoptotic fraction of MPM cells (85) and in 2014, the RNA-interference screening performed on MPM cell-lines confirmed its role in cell-cycle and in the apoptosis (86). CDC2 inhibition with roscovitine reduced MPM cells growth and sensitised cells to cisplatin by 2.5 to 4 fold (86).…”
Section: Clinical Implications Of Overexpressed Genes In Mpmmentioning
confidence: 99%